Levels of cytokines in extended purulent peritonitis and methods of immunocorrection - E. T. Mammadova (Клінічна хірургія)
Objective. Comparative studying of the cytokines secretion dynamics in extended purulent peritonitis in postoperative period on background of the standard basic therapy and its combination with cytokinotherapy.